(untitled) (Sociología y Tecnociencia, 2013)
Scientists are faced with many challenges along their international trajectory as they balance professional and family goals. Certain theoretical frameworks support the concept that career paths are shaped by social and institutional forces in science, whereas other theories point to family constraint factors as the reasoning behind scientists’ decisions to either go abroad or return home. Commonly, women scientists report many challenges when deciding to move internationally. In this paper we aim to exploit data from the Survey on Human Resources in Science and Technology, carried out by the Spanish Statistical Office in 2010, by analysing the life course of 4,123 Spanish doctorate holders. The results indicate there is a strong influence of institutional forces constituting a scientific culture which promotes rules and certain habits about how scientists should progress in their careers. Such forces lead to increasing rates of international mobility. At the same time, the data reveal that decisions about leaving and returning depend on the life course of the doctorate holder, and usually involve some family and personal considerations. Women have adopted a similar career track to men regarding international mobility, although women with children present low rates of high mobility and, by contrast, childless women present higher rates of high mobility than childless men.